Public Policies to Support Entrepreneurship and SMEs. Empirical Evidences from Romania - Sorin Gabriel ANTON; Mihaela ONOFREI (Transylvanian Review of Administrative Sciences, 2016)
Based on a set of variables measured in the Global Entrepreneurship Monitor (GEM) study, we analyzed the entrepreneurial profi le of Romanian economy after the onset of fi nancial crisis. We found a positive attitude towards entrepreneurship in Romania, but the fi nancial crisis started in 2008 severely affected the entrepreneurial environment. In many countries, the lack of an entrepreneurial culture and fi nancial constraints are seen as critical barriers to entrepreneurship. In the light of global fi nancial crisis, the support of entrepreneurial activities has risen as the entrepreneurship has the potential to foster economic recovery. In the second part of the paper we analyze policy actions implemented by the Romanian authorities in order to support SMEs in coping with the effects of fi nancial crisis. We have found that the most used policy tools have been public subsidies for new businesses and loan guarantees. The paper highlights the main weaknesses in the design and implementation of public policies in Romania and recommends some policy action to improve SMEs’ access to fi nance. The results of this study can be useful for improving the local entrepreneurial environment and also for designing new policy actions aimed to improve the SMEs’ access to fi nancing.